DETECTION OF ENTEROTOXIGENIC STAPHYLOCOCCUS ISOLATED FROM THE GOAT MILK SOLD AT SÃO PAULO STATE. - POIATTI, M. L.; SCHOCKEN-ITURRINO, R. P.; RAGAZANI, A. V. F.; HATAYDE, M. C.; GARCIA, G. R. (Ars Veterinaria, 2008)
The aim of this work was to isolate Staphylococcus sp. and detect its capacity in producing enterotoxins. Two hundred fifty five samples of either raw, pasteurized or frozen goat milk from three farms located in the hinterland of São Paulo State, Brazil, were analyzed from April through October 2000. The method described by APHA (1992) was used to isolate the Staphylococcus. The production of toxins was analyzed by the Optimum Sensitivity technique in plates according to ROBBINS and colleagues (1974). Out of 143 positive samples for Staphylococcus sp, 32% were coagulasepositive and 67.3% were determined to be coagulase-negative. Among the coagulase-positive Staphylococci, 27.1% came from raw milk; 1.3% from the pasteurized one, and 4.3% from the frozen milk. Among the isolated raw samples, 10.6% resented Staphylococcal enterotoxins (SE) A and B, where as 6.5% had the A, B and C enterotoxins. These results disclose the potential risk this product could offer to its consuming population, especially because raw milk is mostly used to make several milk products. KEY